Unaccompanied and Separated Syrian Refugee Children: Case Study of a New Feature for Social Work Practice in Jordan. (2nd August 2018) - Suleiman AlMakhamreh, Sahar; Hutchinson, Aisha Jane
Abstract: While Jordan has hosted many refugees within its borders over the past 70 years, the recent influx of Syrian refugees has significantly increased pressure on an already fragile economic and social landscape. The Jordan Response Plan to Syrian Refugees advocates for emergency response that meets the basic needs of refugees alongside long-term capacity building of Jordanian services and infrastructure; with the Protection Working Group (an inter-agency working group with sub groups on child protection, gender-based violence and mental health) specifically advocating for more social workers. While the role of social workers in working with refugees is relatively well established in destination countries (such as the United States, Canada, Australia, parts of Europe), it is less well established in neighbouring and transition countries – countries which are the "first" responders and host the bulk of refugees. By describing a case study on the role of social workers in a foster care programme for unaccompanied and separated Syrian refugee children in Jordan, we establish the contribution that social workers can make to the multi-disciplinary team to improve the short- and long-term well-being of refugees. The article concludes with a number of policy recommendations.